Mediating Peace through Local Tradition of Cross-Religious Community in Saparua Island, Moluccas - Hasbollah Toisuta; Abidin Wakano; Miftahul Huda (el Harakah: Jurnal Budaya Islam, 2022)
On Saparua Island in the Moluccas, Indonesia, local tradition guides the interreligious community of Muslims and Christians. Issues relating to people's races, religions, and ethnic backgrounds frequently spark conflict in the community. At the moment, it is working on maintaining and advancing peace. This article presents an investigation into the factors that contribute to religious harmony in communities comprised of members of different faiths. This research was conducted on Saparua Island through observation and interviews with community figures and members of the religious, academic, youth, and female communities. It was hypothesized, and subsequent research confirmed, that the community adheres to the principles of peace and the way of life espoused by the "Basudara People" in Ale Rasa Beta Rasa, Sagu Salempeng Patah Dua, and Sei Leli Hatulo-Hatuli Eleli Esepei. Peace in the cross-religious community can be achieved through the practice of local traditions like Pela Gandong and Masohi, which are forms of community cooperation. As a consequence of this, the result demonstrates the significance of having dialogues between people of different religious and cultural backgrounds to keep and maintain the viability of interreligious peace. Tradisi lokal di Pulau Saparua, Maluku, Indonesia menjadi panduan moral (norma) bagi kehidupan komunitas lintas agama (Muslim-Kristiani) yang pernah terjadi konflik dipicu isu Suku, Agama, Ras dan saat ini sedang berproses merawat dan membangun perdamaian. Dalam artikel ini, perdamaian komunitas lintas agama dianalisis melalui tradisi lokal sebagai kriterianya. Penelitian ini didasari oleh observasi dan wawancara di antara tokoh adat, tokoh agama, tokoh pemuda, pemerhati perempuan, akademisi, dan masyarakat di Pulau Saparua. Diprediksi dan ditemukan bahwa prinsip perdamaian dari filosofi hidup “Basudara People” pada Ale Rasa Beta Rasa, Sagu Salempeng Patah Dua, dan Sei Leli Hatulo-Hatuli Eleli Esepei. Perdamaian melalui tradisi lokal Pela Gandong dan Masohi sebagai kerjasama untuk saling membantu komunitas lintas agama. Dengan demikian, hasil menunjukkan pentingnya dialogis tokoh lintas agama dan tokoh adat untuk menjaga dan memelihara keberlanjutan perdamaian lintas agama.